Learning through obstacles in an interprofessional team meeting: A discursive analysis of systemic contradictions - Ros, Jenny; Grossen, Michèle (Outlines. Critical Practice Studies, 2020)
Drawing both on cultural-historical activity theory and on a dialogical approach to discourse, this article expands a method of analysis developed by Engeström & Sannino (2011) to capture discursive manifestations of contradictions in an activity system. The data consist of recorded meetings of an interprofessional team working with persons living with both a mental handicap and psychiatric disorders. The mission of this team is to coordinate socio-educative and psychiatric work. A sequence taken from one of these meetings was submitted to a step-by-step discourse analysis and examined how the participants negotiated and managed the obstacles met with in their daily work. The analysis showed how an initial obstacle presented as a conflict was gradually turned into a critical conflict and finally into a dilemma between two rules: professional confidentiality and transparency towards the patient. It showed how the participants collectively coped with this dilemma, and came to define it as a problem related to work organisation, and not only to interpersonal relationships. The study shows the importance of discourse processes in collaborative work and in fostering professional learning and focus upon discourse processes through which team members deal with obstacles in their daily work and to provide a fine-grained analysis of systemic contradictions.